Psychological suffering: A study of young Dental students (Research, Society and Development, 2024)
The aim of this study was to assess the occurrence of psychological distress among dental students at a public university in the municipality of Maceió - Alagoas, Brazil. This study was conducted using a qualitative analytical cross-sectional methodology. The questionnaire was administered virtually to 100 dental students at a public university in Alagoas. The 79 questions were structured into four sections to identify the sociodemographic context, behaviors, and social habits of the participants, and by questions based on the Self Reporting Questionnaire (SRQ-20) and the Beck Anxiety and Depression Scale. Most of the participants in this study were female, brown, single, shared a home with their parents and depended exclusively on them, had a good level of satisfaction with their degree, had regular leisure activities, and had never had psychological or psychiatric treatment. High levels of mental distress were found in this study and are related to excessive workload, normalization of high levels of stress, lack of available time, and financial constraints.